Effect of Preceding Medications on Resuscitation Outcome of Out-Of-Hospital Cardiac Arrest. (March 2017) - Hung, Shih-Wen; Chu, Chien-Ming; Su, Chih-Feng; Tseng, Li-Ming; Wang, Tzong-Luen
As evidence regarding the impact of preceding medications on resuscitation outcomes has been inconsistent, this study aimed to analyze the association between preceding medications and resuscitation outcomes in patients experiencing out-of-hospital cardiac arrest (OHCA). This retrospective study included patients with OHCA presenting to a tertiary care hospital by emergency medical service (EMS) between January 2006 and June 2011. Using the Utstein template, data were collected from EMS and hospital medical records for prehospital care, in-hospital care, and medications which were taken continuously for at least 2 weeks preceding OHCA. Primary outcome was the proportion of patients with a survived event. Multivariable logistic regression analyses were performed to evaluate the predictors of survived events. Among the 1381 included patients with OHCA, 552 (40.0%) patients achieved sustained return of spontaneous circulation and 463 (33.5%) patients survived after resuscitation, 96 (7.0%) patients survived until discharge, and 20 (1.4%) patients had a favorable neurological outcome at discharge. The multivariable analyses revealed that use of statins preceding OHCA was independently associated with a greater probability of a survived events (OR=2.09, 95% CI 1.08 to 4.03, p=0.028).Use of digoxin was adversely associated with survived events (OR=0.39, 95% CI 0.16 to 0.90, p=0.028) in patients with OHCA. The continuous use of statins preceding OHCA was positively associated with survived events, while use of digoxin was adversely related. It deserves more attention on medications preceding OHCA because of their potential effect on resuscitation outcomes.